Optimum Tilt Angle for South Facing Flat Solar Collectors in Duhok City - Na'man, Salahaldin; Yacoob, Haval Y.; Omar, Omar S. (Science Journal of University of Zakho, 2013)
One of the important parameters that affect the performance of a solar collector is its, tilt angle with the horizon. This is because of the variation of tilt angle changes the amount of solar radiation reaching the collector surface. In this paper, the global irradiation observed in Duhok from 1990 to 2007 was used to estimate the optimal tilt angle for solar collectors. The observed data are resolved into diffusion, beam and albedo components. Total solar radiation on the solar collector surface with an optimum tilt angle is computed for specific periods. It is found that the optimum tilt angle changes between 0◦ (June) and 62◦ (December) throughout the year. In winter (December, January, and February) the tilt should be 58◦, in spring (March, April, and May) 20, in summer (June, July, and August) 5◦, and in autumn (September, October, and November) 46.3◦. The yearly average of this value was found to be 32.33◦ and this would be the optimum fixed tilt throughout the year.